Selective activation of adrenoceptors potentiates IKs current in pulmonary vein cardiomyocytes through the protein kinase A and C signaling pathways. (December 2021) - Mi, Xinya; Ding, Wei-Guang; Toyoda, Futoshi; Kojima, Akiko; Omatsu-Kanbe, Mariko; Matsuura, Hiroshi
Abstract: Delayed rectifier K + current ( I Ks ) is a key contributor to repolarization of action potentials. This study investigated the mechanisms underlying the adrenoceptor-induced potentiation of I Ks in pulmonary vein cardiomyocytes (PVC). PVC were isolated from guinea pig pulmonary vein. The action potentials and I Ks current were recorded using perforated and conventional whole-cell patch-clamp techniques. The expression of I Ks was examined using immunocytochemistry and Western blotting. KCNQ1, a I Ks pore-forming protein was detected as a signal band approximately 100 kDa in size, and its immunofluorescence signal was found to be mainly localized on the cell membrane. The I Ks current in PVC was markedly enhanced by both β1 - and β2 -adrenoceptor stimulation with a negative voltage shift in the current activation, although the potentiation was more effectively induced by β2 -adrenoceptor stimulation than β1 -adrenoceptor stimulation. Both β-adrenoceptor-mediated increases in I Ks were attenuated by treatment with the adenylyl cyclase (AC) inhibitor or protein kinase A (PKA) inhibitor. Furthermore, the I Ks current was increased by α1 -adrenoceptor agonist but attenuated by the protein kinase C (PKC) inhibitor. PVC exhibited action potentials in normal Tyrode solution which was slightly reduced by HMR-1556 a selective I Ks blocker. However, HMR-1556 markedly reduced the β-adrenoceptor-potentiated firing rate. The stimulatory effects of β- and α1 -adrenoceptor on I Ks in PVC are mediated via the PKA and PKC signal pathways. HMR-1556 effectively reduced the firing rate under β-adrenoceptor activation, suggesting that the functional role of I Ks might increase during sympathetic excitation under in vivo conditions. Graphical abstract: Unlabelled Image Highlights: The I Ks channel was expressed on the membrane of pulmonary vein cardiomyocytes (PVC). β- and α1 -adrenoceptor stimulation enhanced I Ks in PVC via the PKA and PKC pathway. The I Ks was more potentiated by β2 -adrenoceptor stimulation than β1 -adrenoceptor. The β-adrenoceptor enhanced firing rate was markedly reduced by I Ks inhibition.